Advanced International Training Programme on education for sustainable development in higher education, Sweden, May 1-13, 2011. - Advanced International Training Programme (2011 : Sweden) (Swedish International Development Cooperative Agency], 2011)
This programme seeks to support creative thinking and the development of change projects in the field of Education for Sustainable Development in higher education in Africa and Asia. These can be innovations in teaching, research, community engagement or university policy and management.